Gender Inequality and the Division of Household Labor: a Comparative Study of Middle-class, Working Married Men and Women in Japan and Indonesia - Simulja, Jenny; Wulandari, Endah H.; Wulansari, Sri Ayu (UI Scholars Hub, 2014)
eeking to offer a balanced perspective to gender inequality and the division of household labor among middle-class, working married men and women in Japan and Indonesia, this paper examines the effects of individual-level characteristics (relative income, working hours, gender ideology) as well as the country-level factors (e.g. GEM: Gender Empowerment Measure) on the dynamics of housework distribution between spouses in both countries. Statistical analyses show a number of significant correlations between these variables, among which gender ideology seems to be of particular importance. Perhaps the most enlightening finding of all is that despite their lower GEM rank compared to Japan, the Indonesian respondents have relatively egalitarian division of labor in their households. This finding provides a new insight that GEM, which emphasizes the political economy aspects of a country, may not be sufficient to capture gender disparities without considering other socio-cultural factors in the complexity of day-to-day actual division of housework.